2018
DOI: 10.1111/imr.12705
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT signaling in regulation of innate lymphoid cells: The gods before the guardians

Abstract: SUMMARY Immunity to pathogens is ensured through integration of early responses mediated by innate cells and late effector functions taking place after terminal differentiation of adaptive lymphocytes. In this context, innate lymphoid cells (ILCs) and adaptive T cells represent a clear example of how prototypical effector functions, including polarized expression of cytokines and/or cytotoxic activity, can occur with overlapping modalities but different timing. The ability of ILCs to provide early protection r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 173 publications
0
32
0
Order By: Relevance
“…The in vitro studies show that CXCR4 cooperatively acted with Wnt on β‐catenin signalling activation and fibrotic lesions (Figure ). Meanwhile, SDF‐1α, the ligand of CXCR4, evidently induced the phosphorylation and activation of JAK2/STAT3 and JAK3/STAT6 (Figure ), the two key effectors of signalling cascade in JAK/STAT pathways . Furthermore, overexpression of STAT3 or STAT6 repressed GSK3β transcription, and siRNA‐mediated inhibition of STAT3 or STAT6 could significantly inhibit SDF‐1α‐induced β‐catenin activation and fibrotic lesions (Figure ).…”
Section: Discussionmentioning
confidence: 96%
“…The in vitro studies show that CXCR4 cooperatively acted with Wnt on β‐catenin signalling activation and fibrotic lesions (Figure ). Meanwhile, SDF‐1α, the ligand of CXCR4, evidently induced the phosphorylation and activation of JAK2/STAT3 and JAK3/STAT6 (Figure ), the two key effectors of signalling cascade in JAK/STAT pathways . Furthermore, overexpression of STAT3 or STAT6 repressed GSK3β transcription, and siRNA‐mediated inhibition of STAT3 or STAT6 could significantly inhibit SDF‐1α‐induced β‐catenin activation and fibrotic lesions (Figure ).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, several mutations have been evidenced in STATs, particularly Stat1, Stat3, and Stat5 [3,152]. Altered immune function is common to many of these mutations, including aberrant cytokine signaling and responsiveness, poor Th1 differentiation, IFN dysregulation, loss of NK cell cytotoxicity, abnormal myeloproliferation, and autoimmunity [63,152,153]. As such, many of the effects that LOF and GOF mutations in JAK-STAT pathway members direct in the cancer context are immune-associated.…”
Section: Dysregulation Of Jak-stat Signaling In Cancermentioning
confidence: 99%
“…The JAK-STAT pathway, and specially STAT5 action, is central for milk synthesis by mammary cells (Reichenstein et al 2011). Recent studies have also revealed that the JAK-STAT pathway is closely related to cellular immunity (Stabile et al 2018;Li et al 2019). When STAT5 was abnormally activated, it regulated the expression level of BCL-2 to change cell cycle progression and block apoptosis in several cancer cell lines (Xi et al 2003;Li et al 2005).…”
Section: Discussionmentioning
confidence: 99%